An Exceptional Vulvar Tumor: Myeloid Sarcoma of the Labia Majora. (March 2020) - Ramlakhan, Karishma P.; Groenendijk, Floris H.; Levin, Mark-David; Noorduyn, Leonard A.; Kooi, Sjarlot G.
Abstract : Vulvar malignancies are rare and have diverse origins and presentations. The majority of these tumors are squamous cell carcinoma. An ulcerating vulvar tumor was found in a 74-yr-old woman presenting with fatigue and leukocytosis. Tumor biopsy revealed infiltration of blastoid cells from myeloid origin. Through bone marrow aspiration chronic myelomonocytic leukemia was diagnosed, of which the vulvar tumor was a rare extramedullary disease manifestation termed myeloid sarcoma. Limited palliative treatment was instated with a focus on the patient's quality of life. Myeloid sarcoma (chloroma; granulocytic sarcoma) is a mass of myeloblasts occurring in cases of myeloid disease. Manifestations in most organ systems have been described. Presentation in gynecologic areas is reported in a few case reports, to which we now add our experience.